An Iterative Ray Tracing Algorithm to Increase Simulation Speed While Maintaining Overall Precision - Hanna Autio; Nikolaos-Georgios Vardaxis; Delphine Bard Hagberg (Acoustics, 2023)
Ray tracing is a frequently used method for acoustic simulations, valued for its calculation speed and ease of use. Although it is fast, there are no fully ray tracing-based real-time simulation methods or engines. Under real-time restrictions, ray tracing simulations lose precision and the variance inherent in the random simulation method has too much impact on the outcome. In this paper, an algorithm called iterative ray tracing is presented that reduces the negative effects of real-time restrictions by iteratively improving the initial calculation and increasing the precision over time. In addition, new estimates of the expected value and variance of ray tracing simulations are presented and used to show the iteration steps in the new algorithm reduce variance, while maintaining the expected value. Simulations using iterative ray tracing are compared to measurements and simulations using the classical ray tracing method, and it is shown that iterative ray tracing can be used to improve precision over time. Although more testing is needed, iterative ray tracing can be used to extend most ray tracing algorithms, in order to decrease the adverse effects of real-time restrictions.